"Caring‐about" and the Problem of Overwhelming Obligations. (2016) - O'Dowd, Ornaith
Abstract : Care theorists often think of care as involving (at least) "caring‐about"—concern or attentiveness—and "caring‐for"—acting to nurture, look after, or meet needs. One problem for any theory of care is the scope of our obligations to care in both of those senses; in particular, our capacities for "caring‐about" often outrun our capacities for "caring‐for." Accounts of care as potentially global in scope may ascribe overwhelming obligations to moral agents; however, we are often tempted to avoid or ignore situations that may call for a caring response. I suggest that some Kantian ideas may help to strike a reasonable balance.